2017
DOI: 10.1111/jebm.12255
|View full text |Cite
|
Sign up to set email alerts
|

Use of patient safety culture instruments in operating rooms: A systematic literature review

Abstract: Although patient safety culture is considered important in health care and patient safety, the number of studies in which patient safety culture has been estimated using the instruments in operating rooms, is fairly small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
(314 reference statements)
0
5
0
5
Order By: Relevance
“…Several instruments are available to assess safety culture [ 13 , 14 ]. One of them is the safety attitudes questionnaire (SAQ), which is the most commonly used instrument to measure patient safety culture in hospital operating rooms [ 15 ]. The instrument may identify possible weaknesses in a clinical setting and this can stimulate quality improvement interventions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several instruments are available to assess safety culture [ 13 , 14 ]. One of them is the safety attitudes questionnaire (SAQ), which is the most commonly used instrument to measure patient safety culture in hospital operating rooms [ 15 ]. The instrument may identify possible weaknesses in a clinical setting and this can stimulate quality improvement interventions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new study carried out by (Zhao et al, 2017) with an objective to identify and qualitatively describe, in a literature review, how the instruments were used to evaluate patient safety culture in the operating rooms and published studies. The authors identified 1025 references, of which 99 were obtained for fulltext assessment; 47 of these studies were deemed relevant and included in the literature review.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Por isso, necessita de uma gestão adequada que conduza à melhor eficiência e eficácia, mantendo ou desejavelmente melhorando os atuais níveis de qualidade assistencial (6) . Numerosos estudos têm vindo a salientar a importância da utilização de indicadores de qualidade no centro cirúrgico, monitorizando a qualidade e segurança dos cuidados (7)(8)(9)(10) .…”
Section: Introductionunclassified